2017
DOI: 10.1080/17453674.2017.1350008
|View full text |Cite
|
Sign up to set email alerts
|

Recall and patient perceptions of hip precautions 6 weeks after total hip arthroplasty

Abstract: Background and purposeThere is a lack of evidence to support the role of hip precautions in preventing dislocation following total hip arthroplasty (THA). We report an exploratory study which assesses recall, adherence, and the impact of precautions on activities of daily living in the first 6 weeks postoperatively.Patients and methodsWe designed a new questionnaire based on the education patients receive and refined by professionals within our multidisciplinary team. 129 patients underwent primary elective TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Furthermore, a recent study showed that while most patients can remember all of the restrictions recommended at 8 weeks after surgery only one-fifth adhere to all restrictions, suggesting that even if restrictions are prescribed most patients do not adhere to them (Lee et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study showed that while most patients can remember all of the restrictions recommended at 8 weeks after surgery only one-fifth adhere to all restrictions, suggesting that even if restrictions are prescribed most patients do not adhere to them (Lee et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2016, Lee et al. 2017). Authors KG, AT, and HH drafted the questionnaire, whereafter all other authors were asked to review it.…”
Section: Methodsmentioning
confidence: 98%
“…A proportion of patients post joint replacement are left dissatisfied experiencing some functional disability and may be failing to comprehend their ultimate level of physical function (Wylde et al 2007). Although most participants are informed preoperatively of what physical ability is likely to be postoperatively, including common precautions (Lee et al 2017), perhaps the emphasis on this is not enough. In terms of preoperative education, the addition of realistic activities/hobbies individuals are likely to be able to participate in post surgery may help to meet expectations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cadaveric model allows experimentation and measurements that may not be ethically possible in live patients, while maintaining realistic anatomical and material properties that may not be realized in other laboratory or computational approaches. Our cadaver data may, therefore, help to interpret clinical findings in the early postoperative period when the risk of hip instability is greatest 35,[43][44][45] and may help to determine the need for, and value of, lifestyle restrictions and hip precautions, which continue to be keenly debated 34,[46][47][48][49][50] . It may also be the case that balancing the capsule appropriately at time zero would initiate appropriate biomechanical conditions for better long-term function, but this would certainly need a clinical project to evaluate.…”
Section: Neck Lengthmentioning
confidence: 99%